Money laundering crime in the E.money environment A comparative study in the two of Iraqi and Algerian legislation - Khadidja, Merabet; Mohammed, Hammoudi; Yassen, Sabah (Humanities Journal of University of Zakho, 2022)
The Iraqi and Algerian laws faced the crime of money laundering in the electronic money environment through general criminal texts in order to accommodate the various methods adopted in its commission. The perpetrators of the money laundering crime in the electronic money environment sometimes resort to the exploitation of electronic money in committing it as a facilitating mean. The adoption of this method expands the crime of money laundering and makes it difficult to identify the perpetrators and their places of residence, in addition to tracking the movement of money. Electronic money has many advantages that are exploited by perpetrators to achieve illegal gains, meaning that it is used in a misplaced manner. Though it has been created for electronic commerce, the perpetrators use it to achieve their criminal goals. The coverage of the Iraqi and Algerian legislation, relating the study, for all methods of committing a money laundering crime, including those committed in the electronic money environment, does not mean the actual confrontation as much as it mean the availability of the legal framework of criminalization, because the money laundering crime implemented in the described environment includes a digital technology aspect that requires capabilities of technical expertise to achieve complete confrontation, and that requires specialized persons in information and communication technology.